Ischemic Postconditioning Attenuates Myocardial Ischemia-Reperfusion-Induced Acute Lung Injury by Regulating Endoplasmic Reticulum Stress-Mediated Apoptosis - Li,Aimei (2022)
ABSTRACT Objective: To explore the effect of ischemic postconditioning on myocardial ischemia-reperfusion-induced acute lung injury (ALI). Methods: Forty adult male C57BL/6 mice were randomly divided into sham operation group (SO group), myocardial ischemia-reperfusion group (IR group), ischemic preconditioning group (IPRE group) and ischemic postconditioning group (IPOST group) (10 mice in each group). Anterior descending coronary artery was blocked for 60 min and then reperfused for 15 min to induce myocardial IR. For the IPRE group, 3 consecutive cycles of 5 min of occlusion and 5 minutes of reperfusion of the coronary arteries were performed before ischemia. For the IPOST group, 3 consecutive cycles of 5 min reperfusion and 5 minutes of occlusion of the coronary arteries were performed before reperfusion. Pathological changes of lung tissue, lung wet-to-dry (W/D) weight ratio, inflammatory factors, oxidative stress indicators, apoptosis of lung cells and endoplasmic reticulum stress (ERS) protein were used to evaluate lung injury. Results: After myocardial IR, lung injury worsened significantly, manifested by alveolar congestion, hemorrhage, structural destruction of alveolar septal thickening, and interstitial neutrophil infiltration. In addition, lung W/D ratio was increased, plasma inflammatory factors, including interleukin (IL)-6, tumor necrosis factor (TNF)-α, and IL-17A, were increased, malondialdehyde (MDA) activity of lung tissue was increased, and superoxide dismutase (SOD) activity was decreased after myocardial IR. It was accompanied by the increased protein expression levels of ERS-related protein glucose regulatory protein 78 (GRP78), CCAAT/enhancer-binding protein (C/EBP) homologous protein (CHOP), and caspase-12, and the increased apoptotic indices of lung tissues. Conclusion: IPOST can effectively improve myocardial IR-induced ALI by inhibiting ERS-induced apoptosis of alveolar epithelial cells.